Mapping of Donor Blood Antigens and Development of Panel Cell Reagents in Bali Province - Mulyantari, Ni Kadek; Lestari, Anak Agung Wiradewi; Herawati, Sianny (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Examination of other blood groups' antigens, such as Rhesus (d, C, c, E, e), Kell, Duffy, Kidd, and others, is not routinely carried out in blood services. This study aimed to determine the type of blood group antigen and the composition of the antigens of panel cell reagents for antibody screening and identification in Bali. The subjects were 120 voluntary donors who regularly donate blood. Blood group antigen examination was carried out with a column agglutination test. The antigen mapping was analyzed to determine the possible development of panel cell reagents. Among 120 research subjects, 76.67% were male. Rhesus antigen mapping showed 73.3% DCe phenotype, 3.33% DcE, 3.33% Dce, 19.17% DCE. MNS system, 22.5% M-N+, 35.83% M+N+, 85% S-s+, 14.17% S+s+ and 0.83% S+s-. For the Kell system, no donor with phenotype K+k-, 5.83% K+k+, 94.17% K-k+. No donor with Kpa antigen and 100% with Kpb antigen. Based on Duffy system, 74.17% Fy (a+b), 23.33% Fy(a+b+), 1.7% Fy(a-b+), 0.8% Fy(a-b-). For Kidd system 36.67% Jk(a+b-), 45.83% Jk(a+b+), 17.5% (Jk(a-b+) and no donor with Jk(a-b-). The screening analysis of donor antigens allows the development of panel cell reagents using two types of panel cells. Most donors have a Rhesus DCe phenotype with other dominant antigens, M+N+, S-s+, K-k+, Kpb, Fy(a+b-), and Jk(a+b+). The development of panel cell reagents can be done with the antigen composition of R1R1 (D, C, e, M, S, k, Kpb, Fya, Jka) and R2R2 (D, c, E, M, N, s, K,k, Kpb, Fya, Fyb, Jka, Jkb).